Yearning for Godot: Repetition and Vulnerability in Psychoanalysis. Issue 2 (3rd April 2018) - Haber, Darren
Abstract : This article finds resonance between psychoanalysis and Beckett's landmark play, "Waiting for Godot." In the play, both tramps await Godot; in analysis, participants await markedly different "Godots." Analysands often begin in hope of a concretized or literal "cure" or "savior, " as analysts encounter strongly defended curative fantasies or desires (even demands) for antidotes, while analysts themselves hope for the mutual development of a new relational home for the patient, and empathic understanding of long-sequestered trauma-affect—the very affective experiencing many patients, in this author's experience, have long needed to dissociate or repress via those same stubbornly entrenched defensive processes. The dyadic process is further complexified via the analyst's own developmental hopes of providing "good enough" healing or empathic understanding, which may possibly disappoint an analysand hoping for "cure" or affective bypass—possibly provoking an analyst's own fear of "failing" or disappointing others. The article suggests a way both may find analytic "traction" or relatedness within a fraught intersubjective field.